2009
DOI: 10.4028/www.scientific.net/msf.615-617.609
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Measurement of Electric Discharge Machining for Silicon Carbide

Abstract: Diamond saw is generally used to make the silicon carbide (SiC) wafers from ingots, but it takes long time for cutting. We have used the electric discharge machining (EDM) to cut SiC. The cutting speed of EDM for SiC is almost 10 times faster than the diamond saw, and the surface roughness is 1/10 for the diamond saw. EDM cut SiC by the plasma produced between the wire and SiC material. The emissions from EDM plasma may involve much information for EDM cutting. We monitored the total light intensity by a photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…crystal. To overcome these problems, wiresawing with fixed abrasive (WSFA) and electric discharge machining (EDM) [6][7][8][9] have been developed. The total wafering cost is determined by taking into account the kerf loss, damage depth profile, and wafering time.…”
Section: Introductionmentioning
confidence: 99%
“…crystal. To overcome these problems, wiresawing with fixed abrasive (WSFA) and electric discharge machining (EDM) [6][7][8][9] have been developed. The total wafering cost is determined by taking into account the kerf loss, damage depth profile, and wafering time.…”
Section: Introductionmentioning
confidence: 99%
“…The recent expansion of wafer diameter to 6 inches increases cutting time and arises difficulties supplying abrasive grains to the center of over 6 inches crystal. Overcoming these problems, EDM is developed [1][2][3][4]. It is reported that crystal disorder induced by EDM are comparable to that induced by mirror polish [5].…”
Section: Introductionmentioning
confidence: 99%
“…Since pure SiC material is expensive and high hardness, researchs for low loss and high speed machining are important. In order to slice a large SiC ingot effectively, EDM as an alternative to the diamond wire saw is studied [1][2][3][4]. Schematic image of the conventional EDM is shown in figure 1(a).…”
Section: Introductionmentioning
confidence: 99%